The relationship of climate change awareness and psychopathology in persons with pre-existing mental health diagnoses - Gebhardt, Nadja; Schwaab, Lukas; Friederich, Hans-Christoph; Nikendei, Christoph (Frontiers in Psychiatry, 2023)
Introduction: Persons with pre-existing mental health diagnoses are known to be more vulnerable to the consequences of climate change, such as extreme weather events and rising temperatures. However, it remains unclear if this holds true for adverse effects of climate change awareness, too. Methods: N = 89 patients of a psychosomatic outpatient clinic were assessed with well-established mental health questionnaires (PHQ-9 for depressive, GAD-7 for anxious, and PTSS-10 for post-traumatic symptoms) in their original form and in a modified version (PHQ-9-C, GAD-7-C, PTSS-10-C) specifically asking for patients` symptom load regarding climate change awareness, and instruments evaluating personality factors (OPD-SQS, SOC, RQ). Results: 21% of the sample reported at least mild symptoms of anxiety regarding climate change awareness, and 11% mild symptoms of depression due to climate change awareness. General anxiety (GAD-7) scores significantly predicted if people reported any psychological symptoms due to climate change awareness. In multiple regression analyses, higher scores of clinical symptoms of depression, anxiety or post-traumatic stress predicted higher scores of depressive, anxious or post-traumatic symptoms regarding climate change awareness, and higher scores of psychological symptoms regarding climate change awareness predicted each other. Younger participants reported significantly more traumatic symptoms regarding climate change awareness. Discussion: The reported mental health impairments regarding climate change awareness in persons with pre-existing mental health diagnoses indicate an increased vulnerability. Hereby, depressive mental health burden seems to induce a predominantly depressive processing of climate change resulting in climate chance relateddepression. This holds also true for anxious and traumatic symptoms, and points towards biased attentional and memory processes and mood congruent processing.